Coronary bypass for diabetic heart patients. (March 2014) - Kamalesh, Masoor; Sharp, Thomas
SUMMARY A literature search for clinical trials evaluating the role of bypass surgery for revascularization of diabetics with significant coronary artery disease that reported results in that past 4 years was undertaken. Six clinical trials were identified that recently reported intermediate to long-term outcomes of coronary bypass in diabetic patients. Three studies were conducted exclusively in diabetics, while three represent subset analyses of larger trials. Two meta-analyses of the clinical trial data and several large database studies have been reported in the past few years as well. We will review the major findings of these studies and the implication of their findings for clinical practice. We will also identify areas where persistent uncertainty remains.